Gait Analysis of Ankle Joints of Indonesians at Low, Medium and High Speeds - Robin Novriansyah; Jason Reynald Hadi; Yuriz Bakhtiar; Amin Husni; Rifky Ismail (RSUP Dr. Kariadi, 2024)
Background : Amputation is a loss of body part, and most amputations are lower extremity amputations. The most common is transtibial amputation. After an amputation a person will need a prosthesis. However, up to now there has been no functional prosthesis specifically made for Indonesians who undergo transtibial amputation because the ankle joint gait data that are currently used are European gait data. So it is necessary to measure the normal gait data of Indonesians' ankle joint. The aims of this study was to measure the normal gait data of the ankle joint of Indonesian population Methods : The Research sample is Indonesians aged 18–26 years with normal gait measured by the 2DMA (two-dimensional motion analyzers) at low, medium and high speeds. The resulting data is searched for the mean and standard deviations and then an independent t-test is performed between normal gait data of Indonesians and Europeans Results : Indonesians have a range of maximum dorsiflexion values for low, medium, and high speeds of : 7.9°, 8.3°, 8.9° and maximum plantar flexion for low, medium, and high speeds of 13.4°, 20.6°, 26°. In the comparison test there was a significant difference between the maximum plantar flexion angle of Indonesians and Europeans. Conclusion : Indonesians have a range of maximum dorsiflexion values for low, medium, and high speeds of 7.9°, 8.3°, 8.9° and maximum plantar flexion for low, medium, and high speeds of: 13.4°, 20.6°, 26°. There is a difference between the normal gait of the ankle joint of Indonesians and Europeans.